Sanitasi Lingkungan di Kawasan Ekowisata Bahari Kampung Blekok Kabupaten Situbondo (Studi di Kawasan Desa Wisata Kampung Blekok Kecamatan Kendit Kabupaten Situbondo) - Farisa Desebrina Charisma; Khoiron Khoiron; Globila Nurika; Kholid Maulana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Kampung Blekok Marine Ecotourism Area in Klatakan Village, Kendit District, Situbondo Regency represents a community-based tourism initiative through mangrove conservation, waterbird protection, and coastal ecosystem preservation.  As tourism activities increase, proper environmental sanitation has become essential to fulfilling amenities within the 3A tourism concept and supporting Sapta Pesona principles. This study aims to describe the physical environment, availability of sanitation facilities, and supporting infrastructure in Kampung Blekok, while offering strategic recommendations. Conducted in April 2025, it used a descriptive-quantitative observational method with purposive sampling. Data were gathered through observation, interviews, documentation, and water quality tests. Results indicate that five out of six sanitation components fail to meet health standards. Recommendations focus on enhancing cross-sector collaboration to support sustainable tourism, environmental protection, and improved public health.